Daniel Gottlieb Messerschmidt (1685-1735) Der erste Erforscher Sibiriens Versuch einer Annäherung an einen großen Wissenschaftler - Lehfeldt, Werner (Universitätsverlag Göttingen, 2023)
Daniel Gottlieb Messerschmidt (1685-1735), a physician from Danzig, was sent to Siberia in 1718 by Tsar Peter I, primarily to research the medicinal plants of this vast territory. On his own initiative, Messerschmidt went far beyond this framework and in the course of his expedition of several years (1720-1727), largely on his own, realized a research program that included the disciplines of botany, ornithology, zoology, meteorology, archaeology, linguistics, ethnology. His extremely extensive scientific legacy, including the summary work "Sibiria perlustrata", has remained unpublished to this day, with a few exceptions. In this monograph, Messerschmidt's life and work are presented comprehensively for the first time ever. The most important basis of the presentation is the handwritten estate of the explorer, preserved in the St. Petersburg Academy Archives, the components of which are presented in detail. Although this legacy has remained largely unpublished, the research results achieved by Messerschmidt, particularly in the fields of botany and zoology, already had a considerable impact in the 18th century, which is described in more detail in the book.